Analysis of the Form and Impact of Airfare Discrimination in Indonesia - Simamora, Halasson; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : To analyze the forms of price discrimination in the airline industry in Indonesia and its impact on consumers and business actors.Design/Methode/Approach : The research method used is a qualitative approach with a descriptive method through literature studies from academic journals, policy reports, and official government publications.Research Finding : Based on the results of data analysis, the research findings are (1) various forms of price discrimination exist, including based on time of purchase, class of service, location of purchase, payment method, and customer loyalty programs, (2) the impacts on consumers include price uncertainty, unfair access to transportation, and potential price exploitation through price adjustment algorithms, (3) the impacts on businesses include revenue optimization but also increased regulatory risks and decreased customer loyalty if perceived as unfair.Theoretical contribution/Originality : This paper highlights how price discrimination strategies in the airline industry impact the balance between business optimization and consumer protection in the Indonesian context.Practitionel/Policy implication : More transparent and fair policies are needed in the implementation of pricing strategies to protect consumer rights without hindering fair business competition in the aviation sector.Research limitation : Limited to literature studies without direct empirical analysis of airline pricing behavior in Indonesia.